Sewa Guna Dengan Hak Opsi Dalam Prespektif Hukum Islam - Moh. Ulumuddin; Ahmad Insya’ Ansori (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2022)
Background. Operationally, finansial lease transaction focuses more on the financing aspect of the Lessor given to the lesse, where the lesse will bear all aspects of maintenance and responsibility for the goods he rents.Aim. This study aims to examine financial leases in the perspective of Islamic law.Methods. This type of research is a qualitative research with a descriptive approach that uses the literature study method as the completion methodology. With the object of research, the Leasing case is seen from the point of view of Islamic law, and how Islam answers these problems.Results. From the point of view of Islamic law, finance leasing transactions tend to be similar to the concept of ijarah or ijarah vomitiyah bi al-tamlik which is used as the basis for making the DSN MUI fatwa on shari'ah leasing. This fatwa provides an overview of the legal basis, rights and obligations of the Lessor, Lessee and other parties involved in this contract. Applicatively, as long as it does not harm either party, the financial leasing law is basically allowed.